Does competition enhance performance or cheating? A laboratory experiment - Christiane Schwieren; Doris Weichselbaumer (Johannes Kepler University of Linz, Department of Economics, 2008)
In this paper we experimentally test whether competing for a desired reward does not only affect individuals performance, but also their tendency to cheat. Recent doping scandals in sports as well as forgery and plagiarism scandals in academia have been partially explained by competitive pressures, which suggests a link between competition and cheating. In our experiment subjects conduct a task where they have the possibility to make use of illegitimate tools to better their results. We find that women react much stronger to competitive pressure by increasing their cheating activity while there is no overall sex difference in cheating. However, the effect of competition on womens cheating behavior is entirely due to the fact that women, on average, are doing worse with respect to the assigned task. Indeed we find that it is the ability of an individual to conduct a particular task and not sex that crucially affects the reaction to competition. Poor performers significantly increase their cheating behavior under competition which may be a face-saving strategy or an attempt to retain a chance of winning.
Keywords: C91; J24; J31; M52; 330; competition; tournament; piece rate; cheating; experiment; Wettbewerb; Betrug; Anforderungsprofil; Akkordlohn; Test